A Rare Cause of Newborn Apnea That Has Not Been Seen for A Very Long Time with the Effect of the Vaccine: Pertussis - Kürşad Kemal Kara; Mutlu Uysal Yazıcı; Nursel Kara Ulu; Nursel Atay Ünal; Hasan Tezer (Galenos Yayinevi, 2023)
Pertussis, caused by Bordetella pertussis, is an important cause of morbidity and mortality in newborn and infancy. Pertussis is diagnosed clinically. It is confirmed by microbiological-serological tests. In recent years, polymerase chain reaction method has also been used in diagnosis. Macrolide group antibiotics are used in the treatment. Pertussis can occur at any age. However, it can cause mortality in infants who have not been vaccinated. A case report is presented in a 30-day-old newborn patient who was admitted to the pediatric intensive care unit due to apnea and respiratory superficial, and Bordetella pertussis was found to be the causative agent.